Clinic Design for Safety During the Pandemic: Safety or Teamwork, Can We Only Pick One?. (July 2022) - Lim, Lisa; Zimring, Craig M.; DuBose, Jennifer R.; Fischer, Gary M.; Stroebel, Robert
Objective: This article aims to illustrate the design considerations of team-based primary care clinics in response to the pandemic. Background: Due to COVID-19, physical distancing became a critical practice in our daily life, especially in healthcare settings where healthcare professionals must continue providing care to patients despite the manifold risks. Many healthcare facilities are implementing physical distancing in their clinic layouts, and healthcare professionals are adjusting their behaviors, so they can stay away from each other. Methods: A total of four team-based primary care clinics were studied to identify their lessons learned regarding safety measures and space usage during the pandemic. Results: The four team-based primary care clinics made changes to the clinic design (e.g., waiting areas, exam rooms, team workspaces), operational protocols (e.g., in-person huddles, social gatherings, staff work locations), and usage of spaces (e.g., outdoor spaces, utility rooms). Such changes enabled the implementation of safety measures during the pandemic. However, healthcare professionals also reported challenges regarding their team communication and coordination due to physical distancing and separation. Conclusions: Our findings suggest that the physical distancing may in fact contribute to less effective teamwork and patient care and negatively affect staff well-being. In this article, we ask healthcare system leaders and designers to continue supporting both safety and teamwork by paying attention to the flexibility and spatial relationships among healthcare professionals rather than fully sacrificing teamwork for safety. Also, now is the time when multidisciplinary collaborations are needed to establish and validate guidelines that can improve both factors.